Decentralization and School Management in Namibia: The Ideologies of Education Bureaucrats in Implementing Government Policies. (9th April 2012) - Pomuti, Hertha; Weber, Everard
Abstract : This paper defines ideology as the belief systems, attitudes, views, and mindsets of educationists which inform their work. It examines the ideologies of school inspectors, principals, and teachers in the implementation of decentralized, cluster-based educational change in Namibia (see Pomuti 2009). Data were collected in three diverse school clusters. Data analyses resulted in the ideologies of the educationists being characterised as authoritarian, bureaucratic, and managerial. The paper argues that while the postapartheid Namibian government has changed the governance structures in education, it has not succeeded in changing the mindsets and actions of important reform implementers. These have more in common with the apartheid system than with the participatory, collaborative, and democratic ideas upon which cluster-based school management in the new Namibia is based.